Designing sustainable antioxidant and anti-inflammatory ingredients from seaweeds for functional gummies - Bruno Toribio de Lima Xavier; Marcelo Franchin; Nima Mohammadi; Carolina Girotto Pressete; Lusânia Maria Greggi Antunes; Yandong Xu; Kai Wang; Jason Bennett; Daniel Granato (Future Foods)
Atlantic wakame (AW) and sea lettuce (SL) are edible seaweeds commonly produced in Asia and Europe, typically consumed as fresh or dried biomass. Because of the short shelf life, developing new post-harvest treatments, such as the extraction of bioactive compounds, is essential for establishing reliable macroalgae supply chains for food applications. This study aims to develop a sustainable and functional seaweed-based food ingredient rich in bioactive compounds for functional food applications. The results indicated that ultrasound-assisted extraction using 70% ethanol for 10 min was optimal for both SL (410±23 mg of gallic acid equivalent [GAE] per kg) and AW (666±63 mg GAE/kg). Both extracts exhibited chemical antioxidant activity and inhibited the protection of human plasma against chemically induced oxidation. SL extract did not exhibit free radical scavenging activity (DPPH). Importantly, no cytotoxicity (IC50>250 µg/mL) was observed in human-derived THP-1, HUVEC, HT-29, and HepG2 cell lines, ensuring the relative safety of these extracts for potential food technology applications. AW and SL extracts (100 µg/mL) reduced intracellular reactive oxygen species generation in lipopolysaccharide (LPS)-challenged THP-1 cells by 66% and 30%, respectively, highlighting the higher antioxidant activity of AW extract. AW and SL extracts did not modulate TNF-α and IL-6 secretion to show anti-inflammatory activity. Gummies infused with AW and SL extracts had a higher total phenolic content than commercial products, but their antioxidant activity was lower. Sensory evaluation revealed that gummies containing seaweed extracts received lower scores for colour, taste, overall impression, and purchase intention than those without extracts.